Compressive strength evaluation of circular tubular short columns with locally corroded ends. (October 2018) - Kim, Hyoung-Seok; Dao, Duy Kien; Shin, Chang-Hee; Jeong, Young-Soo; Kim, In-Tae
Abstract: When structural steel members are in contact with horizontal members, such as concrete slabs, dust and moisture easily accumulate at their junction. This can induce local corrosion at their ends, and consequently, reduce their compressive strengths. In this study, compressive tests were conducted on circular tubular short columns to examine the change in compressive strength with local corrosion at the ends of the columns. The columns were fabricated to have corrosion levels of various depths, heights, and circumferences. As a result, local buckling occurred near the column ends. Moreover, residual compressive strengths linearly decreased as the corroded depth, height, and circumference increased. An evaluation method using the effective volume was proposed to assess the residual critical compressive strengths of circular tubular short columns with locally corroded ends. Highlights: Change in compressive strength with local corrosion at the bottom end of column. Corrosion occurred at the contact of column and transverse member. Corrosion level of different depth, height, and circumference. Relationship between corrosion level and compressive strength. Evaluation equation of compressive strength using effective volume ratio.